2020
DOI: 10.7759/cureus.8325
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Bridles for Securing Nasoenteric Feeding Tubes: A Review of Clinical Effectiveness and Potential Complications

Abstract: Inayat et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Ainda sobre os insumos para a realização da fixação do cateter nasoenteral, estudo destacou o risco aumentado de lesões cutâneas quando utilizado esparadrapos e adesivos transparentes; e lesão por pressão, lesão interna no nariz e epistaxe, no caso de tensão do freio nasal 2 . Pesquisas americanas relataram ocorrências de avulsão espontânea do imã do sistema de freio nasal durante o procedimento de inserção, com a necessidade de realização de endoscopia digestiva para retirada do corpo estranho 14,15 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ainda sobre os insumos para a realização da fixação do cateter nasoenteral, estudo destacou o risco aumentado de lesões cutâneas quando utilizado esparadrapos e adesivos transparentes; e lesão por pressão, lesão interna no nariz e epistaxe, no caso de tensão do freio nasal 2 . Pesquisas americanas relataram ocorrências de avulsão espontânea do imã do sistema de freio nasal durante o procedimento de inserção, com a necessidade de realização de endoscopia digestiva para retirada do corpo estranho 14,15 .…”
Section: Discussionunclassified
“…As fixações realizadas na pele com fita hipoalergênica microporosa ou esparadrapo são as mais comumente utilizadas em diferentes países e contextos 19 . Registra-se alta incidência de remoção não planejada do cateter nasoenteral, seja por pacientes com nível de consciência alterado ou durante os cuidados de enfermagem 1,6,13,14 .…”
Section: Discussionunclassified
“…Dressing used to adhere tube to the cheek or neck Tube is less visually distracting Works well for small, soft tubes; including dressing close to naris adds to security and may reduce "pistoning" or movement of the tube at the naris May be at increased risk for skin breakdown 81 Need to ensure bridle clip does not place pressure on nares resulting in pressure injury [82][83][84] It could also result in internal injury if the tube gets caught or pulled on if allowed to hang from the nose Can be cost-effective as compared with tape, owing to less tube displacement with the bridle 85 Securing the neck lends extra stabilization Devices associated with reported complications such as nasal bleeding [86][87][88][89] facilities have developed policies and procedures for placing feeding tubes during the day while having the bedside RN place an OG or NG tube if enteral access is needed on evening or night shifts. 14 Placing an NG tube instead of an NE tube on "off" shifts may not be ideal, but each facility must weigh the risks vs the benefits of this practice based on the training and availability of their staff.…”
Section: Transparent Dressingmentioning
confidence: 99%
“…Two studies also identified a statistically significant difference in the incidence of skin complications; nasal bridles were associated with a higher rate of nasal ulcerations than the rate in patients with feeding tubes secured with adhesive tape 9,18 . Other types of adverse events not reported in these studies, such as the nasal bridle insertion stylet being retained in the nasal cavity, have been reported in case reports 19,20 . Finally, many previous studies applied the nasal bridle securement device to all patients requiring a small‐bore feeding tube in their setting, 7–11,13–18 which is not how it is always applied in clinical practice (ie, reserving its use to only patients at highest risk of inadvertent tube dislodgement).…”
Section: Introductionmentioning
confidence: 97%
“…9,18 Other types of adverse events not reported in these studies, such as the nasal bridle insertion stylet being retained in the nasal cavity, have been reported in case reports. 19,20 Finally, many previous studies applied the nasal bridle securement device to all patients requiring a small-bore feeding tube in their setting, [7][8][9][10][11][13][14][15][16][17][18] which is not how it is always applied in clinical practice (ie, reserving its use to only patients at highest risk of inadvertent tube dislodgement).…”
Section: Introductionmentioning
confidence: 99%